2013
DOI: 10.1177/0093854813508286
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Victimization on Routine Activities

Abstract: Is there a relationship between victimization and subsequent behaviors, and if so, does victimization lead to risky or constrained activities? Previous research is mixed, possibly due to limitations associated with selection bias, cross-sectional data, and floor and ceiling effects. The current study examines how victimization influences lifestyles using longitudinal National Crime Victimization Survey data. To avoid problems of selection bias and spuriousness, we use a propensity score matching approach to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Although the full body of research is somewhat mixed with respect to this proposition (e.g., Averdijk 2011; Bunch et al 2014;Ousey et al 2008), there is some key evidence to support it. Miethe et al (1990), for example, examined individual lifestyle patterns over two time points and found that the odds of repeat victimization were highest among individuals who continually engaged in risky activities.…”
Section: Structural Disadvantage and The Context Of Victimizationmentioning
confidence: 99%
“…Although the full body of research is somewhat mixed with respect to this proposition (e.g., Averdijk 2011; Bunch et al 2014;Ousey et al 2008), there is some key evidence to support it. Miethe et al (1990), for example, examined individual lifestyle patterns over two time points and found that the odds of repeat victimization were highest among individuals who continually engaged in risky activities.…”
Section: Structural Disadvantage and The Context Of Victimizationmentioning
confidence: 99%
“…Social withdrawal as a consequence of victimization may additionally impair well-being, and collectively weaken the social cohesion and capacity for social control in neighborhoods (Hipp and Steenbeek 2016;Hipp and Wickes 2017;Skogan 1990; Warner and Rountree 1997). However, two studies based on the National Crime Victimization Survey found little or no evidence for a reduction of risky lifestyles subsequent to victimization, based on two survey items on the frequency of shopping and night activity (Averdijk 2011;Bunch et al 2014). Among delinquent adolescents and particularly in neighborhood contexts of concentrated disadvantage and possibly subcultural norms, victimization has been found to actually increase risky lifestyle activities (Turanovic et al 2018).…”
Section: Negative Consequences Of Victimization and Other Life Eventsmentioning
confidence: 99%
“…A major research obstacle is that most extant literature has used cross-sectional survey data and compared individuals who experienced victimization to individuals who did not, leaving results vulnerable to selection bias and unobserved heterogeneity (Bunch et al 2014;Hope 2007). This between-person approach is unable to determine whether differences in well-being have actually been triggered by the victimization event, or whether individuals who experienced victimization already exhibited lower levels of well-being prior to the event (Skogan 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, crime victimization is said to have far-reaching consequences, such as involvement in delinquency and the reproduction of violence (Hay & Evans, 2006). Nevertheless, reactions to the act of violence are not homogenous (Bunch et al, 2014). Traumatic effects may be linked to psychological attributes such as self-efficiency (Bosmans & Velden, 2015); interaction attributes like social connections (Fox & Bouffard, 2015), and social traits, such as poverty (Lowe et al, 2014).…”
Section: Individual-level Effects (Victims and Offenders)mentioning
confidence: 99%